(untitled) (Bangladesh Journal of Neuroscience, 2026)
Background: Peripheral neuropathy is one of the common complications of DM may proceed by a long period of clinically silent impaired glucose tolerance, altering the nerve function by the time diabetes is diagnosed. Nerve conduction study (NCS) remains the most reliable, accurate and sensitive measure for diagnosis of peripheral neuropathy. Objectives: Evaluation of nerve conduction study of newly diagnosed type -2 diabetic patients either and to find out its correlation with glycosylated hemoglobin (HbA1c). Method: This case control study, 50 newly diagnosed type-2 diabetic patients within 1 month of both sex and rest 50 healthy controls were studied during 2018-2020 from outpatient department of Endocrinology and advised to attend the department of Neurology of Dhaka medical college hospital. Nerve conduction study of cross limbs was performed. Blood sugar and glycosylated hemoglobin (HbA1C) were determined. Results: Motor nerve conduction parameters are more affected. Median nerve impairment in both motor and sensory nerve conduction study was statistically significant (p<0.05) between case and control group. Most abnormal parameter is CMAP of peroneal nerve 42% followed by DL of tibial (20%) and median (18%) in motor nerve conduction study whose majority of them HbA1C was >10%. Combined tibial and peroneal nerve involvements were more common 11 (22.0%). In multivariate regression analysis, HbA1C significantly (p<0.05) associated with tibial F-Lat but otherswere not significantly associated. There were significant positive correlation with median DL (r=0.829; p=0.002), median F-Lat (r=0.814; p=0.001), Tibial DL (r=0.805; p=0.004), tibial F-Lat (r=0.832; p=0.001), median sensory DL (r=0.824; p=0.002). Conclusion: Increased HbA1c level indicative of a state of hyperglycemia is a risk factor for polyneuropathy in diabetic patients. NCS parameters are valuable for identification, future prediction of diabetic neuropathy as well as quantitative measure of its severity.